Experimental and theoretical approach of the hydrolysis of pelleted magnesium alloys scraps - Gouty, Q.; Castro, Facundo; Urretavizcaya, Guillermina; Sabatier, J.; Bobet, J. L. (Elsevier Science SA, 2022)
Fil: Gouty, Q.. Universite de Bordeaux; Francia